2005
DOI: 10.1111/j.1442-200x.2004.02004.x
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of activated eosinophils in infants with severe atopic dermatitis

Abstract: Evaluation of eosinophil activation and early therapeutic intervention is mandatory for the treatment of severe AD during infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…62 In AD, its expression on eosinophils was associated with high IgE levels and active inflammation, 63 and data from other allergic diseases indicate that CD69 promotes the inflammatory process. 64 Our data show that CD69 is the only activation marker higher in children vs. adults with AD.…”
Section: Discussionmentioning
confidence: 99%
“…62 In AD, its expression on eosinophils was associated with high IgE levels and active inflammation, 63 and data from other allergic diseases indicate that CD69 promotes the inflammatory process. 64 Our data show that CD69 is the only activation marker higher in children vs. adults with AD.…”
Section: Discussionmentioning
confidence: 99%
“…Although our case before prednisolone (1.5 mg/kg/day) treatment presented with marked hypereosinophilia (21 800/µL) almost 50 times higher than that in disease control, namely, acute asthma (4.0 ± 0.4 years old), the eosinophil cationic protein (ECP) level was almost comparable to that of acute asthma (eosinophil counts, 21 800 vs 442.3 ± 70.0/µL; ECP levels, 23.3 vs 30.2 ± 4.4 ng/mL), as shown in Table 1. Figure 1 shows that the expression of CD69, an activation marker of eosinophils, 4 on peripheral eosinophils in our case was minimal compared with a patient with severe atopic dermatitis as positive control. Serum concentrations of T helper (Th)2 cytokines including interleukin (IL)‐4 and IL‐13 before treatment were markedly elevated compared with those of acute asthma (IL‐4, 78.9 vs 26.2 ± 4.2; IL‐13, 99.8 vs 5.1 ± 0.8 pg/mL).…”
Section: Case Reportmentioning
confidence: 72%
“…Interestingly no association was found with either sex, however many studies have reported males to have raised IgE levels [49]. According to Toma et al [50], infants suffering from severe allergic diseases have significantly higher number of eosinophils and eosinophilic nuclear lobes, platelets, and total serum IgE level. Studies over the past 2 decades have shown that eosinophils play a major role in allergic diseases, characterized by activated eosinophils in the peripheral blood and in the lesional skin [51].…”
Section: Discussionmentioning
confidence: 97%